User experiences of patients with post-acute COVID-19 syndrome receiving occupational therapy telerehabilitation - Kok, Lynn H. J.; Gu, Jenny T.; Kung, Jessica T. Y.; Liang, Shera S.; Gonzalez, Pablo Cruz; Toh, Fong Mei; Sin, Emily; Fong, Kenneth N. K. (Frontiers in Human Neuroscience, 2025)
BackgroundPatients with post-acute COVID-19 syndrome, also referred to as “long COVID,” may face persistent physical, cognitive and psychosocial symptoms which can be challenging to manage given the strict social distancing measures imposed during the pandemic. Telerehabilitation (TR) became increasingly common during COVID-19 pandemic and has been applied to post-acute COVID-19 conditions in previous clinical studies, and it was reported that patients’ symptoms were alleviated and their overall health improved. This study examined the usability and acceptability of TR by occupational therapists delivered for patients suffering from post-acute COVID-19 in Hong Kong.MethodsIn this mixed-methods usability study, participants rated items on the System Usability Scale (SUS) and completed a semi-structured questionnaire via audio-recorded telephone calls. Descriptive data were used to summarize the quantitative data, and thematic analysis was applied to analyze the qualitative data.ResultsTwelve participants (mean age 56.5 years) who had completed a 6-week TR program via the Caspar Health system were recruited for the study. A median SUS score of 56.25 was reported for its usability, despite 83% of the participants viewed the TR system as fairly acceptable. Four themes, namely perception of using the TR system - performance expectancy of TR, other psychosocial and environmental factors, and intention to use TR, were generated on the basis of the participants’ interviews. Most participants reported their willingness to continue using TR and that they would recommend it to other patients.ConclusionMost of the participants were receptive to TR and perceived health benefits from its use. Future research could consider integrating the perspectives of both occupational therapists and patients to generate a more comprehensive understanding of the facilitators of and the barriers to TR for patients who experience long COVID.